Pelaksanaan Hukum Cambuk Sebagai Hukuman Ditinjau Berdasarkan Filsafat Hukum Islam - Lubis, Syaddan Dintara; Ananda, Faisar; Nurasiah, Nurasiah (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2025)
Abstract This study aims to examine the implementation of caning punishment reviewed based on Islamic legal philosophy, as in Islam caning punishment is a punishment for perpetrators of criminal acts where the aim is to provide a deterrent effect for the perpetrators of the crime, the formulation of the problem in this study is how is the implementation of caning punishment in Aceh? And how is the implementation of caning punishment reviewed from Islamic legal philosophy, the research method used in this study is normative legal research. The results of this study are Caning punishment in the review of Islamic legal philosophy can be seen from various perspectives that include the values of justice, welfare, and the main purpose of the application of the punishment itself. In Islam, the law has a very strong basis both in the Qur'an and the hadith, which emphasizes the balance between justice and mercy. Caning punishment, which is included in the category of hudud (punishment clearly stated in the text of the sharia), serves to enforce religious rules while providing a deterrent effect on perpetrators of crimes.Kata Kunci: Hukum Cambuk, Hukuman, Filsafat Hukum Islam Keywords: Caning law, punishment, Islamic legal philosophy